Sequestration of Aristolochic Acids from Meridic Diets by Larvae of Battus Polydamas Archidamas (Papilionidae: Troidini) - Urzua-Moll, A (Czech Academy of Sciences, 2011)
Larvae of the butterfly, Battus polydamas archidamas (Papilionidae: Troidini) feed exclusively on aristolochic acid (AAs)-containing Aristolochia species (Aristolochiaceae). The distribution of sequestrated AAs in the tissues (body, integument and osmeterial secretions) of B. polydamas archidamas larvae during their development, when fed on a meridic diet containing either a higher or lower concentration of AAs (AAI and AAII) than occurs naturally in the aerial tissues of their host plant, was determined. Accumulation of AAs in the body and integument was proportional to the weight of larvae and greater in the larvae that fed on the diet containing the higher concentration of AAs. Phenolic AAs (AAIa and AAIVa) not present in the diets were found in all larval tissues examined. Integument and body extracts had a higher AAI/AAII ratio than in the original diet and also a relatively high AAIa/AAIVa ratio, suggesting a preferred AAII to AAIa transformation in those larval tissues. In the osmeterial secretion, the value of the AAI/AAII ratio was similar to that in the diets and the AAIa/AAIVa ratio close to 1, which suggests that hydroxylation of AAI to AAIVa and of AAII to AAIa occur to similar extents. The higher accumulation of AAs and the relatively higher proportion of AAI, one of the most toxic AAs, in the integument, suggest that their role is to deter attacks by natural enemies.
Keywords: Lepidoptera; Papilionidae; Battus polydamas archidamas; Aristolochia chilensis; aristolochic acids; sequestration of toxins; uptake of toxins